LIFE WITH LESS, LESS WASTE: PROMOTING LIFE SUSTAINABILITY AWARENESS - Nurainingsih; Nur Fadillah, Ega (Journal of English Education and Teacher Trainer, 2024)
The aim of this study is to promote living the life with less which will impact less waste production and practicing life sustainability. Life with less means being minimalist. Being minimalist means less waste and we are practicing sustainability of life. Why is this so important? People should be aware and realize our standard of living is physically and environmentally unsustainable. Waste is one of our biggest problems in our country, take a look in some of our seas there are tons of waste everywhere. It’s not only polluting the environment but it’s also threatening the creatures which live in it. The fact of plastic waste needs 1000 years to be fully decomposed, while decomposing it will contaminate the soil. By practicing life with less the goal of less waste and the awareness of living sustainability life will help the world we are living to be healthier for the next thousands of years. The action needs to be done by ourselves, and one of the educational institutions' duties is to spread the issue to the educator practitioners and the whole ecosystem in order to be more aware and to practice everything that needs to be done. The research uses the netnography, it is one of qualitative research methods which is initiated by consumer research name Robert Kozinets.